Characterization of a low expression haplotype in canine glutathione S‐transferase (GSTT1) and its prevalence in golden retrievers. (25th August 2017) - Craft, S.; Ekena, J.; Mayer, B.; Thamm, D. H.; Saba, C.; Chun, R.; Trepanier, L. A.
Abstract : Glutathione S‐transferase‐theta (GSTT1) is a carcinogen detoxification enzyme, and low activity variants are associated with lymphoma in humans. We recently found a variant in the 3′ untranslated region (UTR) of canine GSTT1, *101_102insT, which was predicted to change miRNA binding and was found in 5 of 17 golden retriever (GR) dogs with lymphoma but none of 14 healthy GRs. The aim of this study was to determine whether this variant led to decreased GSTT1 expression and was a discernible risk factor for lymphoma within the GR breed. On resequencing, *101_102insT appeared to be in complete linkage disequilibrium with 3 additional 3′UTR variants, leading to the inferred haplotype *3T>C; *101_102insT; *190C>A; *203T>C. In canine livers that were heterozygous for this variant haplotype, GSTT1 protein expression was significantly lower compared to the reference haplotype (densitometry .40 vs .64, P  = .022), and GSTT1 transcript levels by qPCR were also significantly lower (fold difference .52, P  = .012), without evidence of substantial allelic expression imbalance. The variant haplotype led to >50% decrease in expression in vitro (.31 ± .07 vs .64 ± .19; P  = .019). We found no significant difference in minor allele frequencies between 71 GR dogs with lymphoma (MAF .162) and 33 healthy age‐matched controls (MAF .136, P  = .69). Our results indicate that the variant GSTT1 3′UTR haplotype containing *101_102insT reduces gene expression, which could lead to impaired carcinogen detoxification, but was not a detectable risk factor for lymphoma in GR dogs.